On UAV Selection and Position-Based Throughput Maximization in Multi-UAV Relaying Networks - Singh, Sandeep Kumar; Agrawal, Kamal; Singh, Keshav; Li, Chih-Peng; Huang, Wan-Jen (IEEE access, 2020)
Due to flexibility in deployment and high mobility, unmanned aerial vehicles (UAVs) can improve the performance of cellular networks. In this paper, we focus on the UAV-assisted cooperative communication network where multiple UAVs serve as relays between a pair of ground users. Based on signal-to-noise ratio (SNR), we propose two UAV selection strategies namely best harmonic mean (HM) and best downlink SNR (BDS). Then, we derive the closed-form expressions for the outage probability, throughput and coverage probability of both the selection strategies. Furthermore, an optimization problem for maximizing the throughput is formulated, subject to the 3-D coordinates (i.e., x, y, and z coordinates) constraint of the selected UAV. The concavity of the problem is analyzed with respect to the horizontal placement of the selected UAV. Next, we propose algorithms to find optimal and sub-optimal position/coordinates of the selected UAV. Computer simulations validate the accuracy of the derived expressions, and demonstrate that BDS selection strategy has a significant performance gain at low SNR values, whereas both the selection schemes attain a similar performance at high SNRs.